VD_FINDINFO AP / 2009 / 161 vom 21. August 2009 - VD Tribunal cantonal (2009)
CAPACITÉ DE CONDUIRE, CANNABIS, DÉLÉGATION LÉGISLATIVE | 55 al. 7 LCR, 91 al. 2 LCR, 19a ch. 1 LStup, 19a ch. 2 LStup, 2 al. 2 OCR, 2 al. 2bis OCR